Microorganisms Profile and their Antimicrobial Resistance Pattern Isolated from the Lower Respiratory Tract of Mechanically Ventilated Patients in the Intensive Care Unit of A Tertiary Care Hospital in Dhaka (Journal of Medicine, 2016)
Objective: Aim of the study was to know the microorganisms profile and determine the antibiotic resistance pattern of the LRT isolates from mechanically ventilated (MV) patients admitted to the ICU. This prospective observational study was done in Department of Critical Care Medicine (ICU) of BIRDEM General Hospital Dhaka from July, 2011 to December, 2011.Methods: Blind Tracheal Aspirate or Broncho Alveolar Lavage or both from 110 consecutive patients (total 130 samples) admitted to the ICU requiring MV were cultured, identified, and antibiotic sensitivity was performed by standard methods.Results: A total of 130 samples were analyzed. Growth was obtained in 93.8% of the samples yielding 143 organisms. Many (21 samples) yielded more than one organism. The major organism isolated were Acinetobacter sp. (54.5%), Pseudomonas sp.(14.7%), Klebsiella sp. (7.7%).Candida sp. (7.0%), Staphylococcus aureus(7.0%), Escherichia coli (4.9%).Proteus and Flavobacterium accounted for 4.2% of the isolates. All the isolates were highly resistant (>90%) to cephalosporins and >70% to fluoroquinolones. The frequency of third generation cephalosporin resistant E. coli, Klebsiellaand imipenem resistant Pseudomonas and Acinetobacter were>90%. Acinetobacter was remarkably resistant to most antibiotics including imipenem (>90% resistant) and Piperacillin+Tazobactum (>85% resistant), but most of the members of the Enterobacteriacae group and Acinetobacter showed maximum sensitivity to colistin (80%-100%).Conclusion: Nonfermenters Gram Negative Bacilli (GNB)-Acinetobacter sp. & Pseudomonas sp. are the most common etiological agents of LRT infections in ICU. There is an alarmingly high rate of resistance to cephalosporin and ²â-lactamase inhibitor group of drugs. Colistin was found to be the most sensitive drug against all GNB.J MEDICINE July 2016; 17 (2) : 91-94